Effect of routine lactation consultant support to mothers on breastfeeding efficacy - Gogi, Vinay Kumar; Shekharappa, Chandrakala Bada; Selvam, Sumithra (Indian Journal of Child Health, 2018)
Introduction: Studies have concluded that lactation consultant’s visit provides more face-to-face time and education than physician support alone in improving the breastfeeding efficacy and rates. Objectives: The objective is to study the effect of incorporating routine lactation consultant to daily postnatal rounds with the resident on (a) cumulative weight loss of postnatal neonates and (b) jaundice requiring phototherapy, number of breastfeedings per day, duration of hospital stay and NICU admission. Methodology: A cross-sectional study was carried out among all stable neonates admitted in postnatal wards weighing >2 kg and gestation >35 weeks. The babies whose mothers were trained on breastfeeding by the pediatric resident doctor, in the routine postnatal rounds, were considered as Group 1. Infants whose mothers were counseled by the lactation consultant and the resident doctor on the breastfeeding were considered as Group 2. The baseline characteristics of mother and the neonates were recorded by a structured proforma. Results: Of 158 eligible babies, during the study period, 84 babies were enrolled for the study. The mean gestation of the babies in Groups 1 and 2 was 38.1±1.9 and 38.2±1.8 weeks, and the mean weight was 2.95±0.42 and 2.87±0.04 kg, respectively. The cumulative weight loss was 5.43±2.53% and 5.59±2.35 % (p=0.75) in Groups 1 and 2, respectively. The duration of hospital stay was 5.6±1.98 and 5.1±0.81 days (p=0.09), jaundice requiring phototherapy 22 (47%) and 15 (37%) with p=0.56 and the number of breastfeedings per day was 10.2±2.98 and 10.5±1.2 times with p=0.60 between the Groups 1 and 2, respectively. Conclusion: Even though there was no difference in either the primary or secondary objective between the groups, postnatal lactation counseling is very essential for improving the breastfeeding efficacy with the support of either doctor or the lactation consultant. There was acceptable cumulative weight loss, urine output, number of breastfeedings per day, and NICU admissions.